Senyawa Fenolik dari Daun Tanaman Kalanchoe prolifera (Crassulaceae) - Yenny Febriani Yun; Lilis Siti Aisyah; Tri Reksa Saputra; Arif Rahman Hakim; Sari Purbaya; Tati Herlina; Euis Julaeha; Achmad Zainuddin; Unang Supratman (Jurnal Kimia Valensi, 2017)
Phenolic compounds such as kaempferol (1), quercetin (2), and methyl caffeate (3) have been isolated from the ethyl acetate extract of Kalanchoe prolifera (Crassulaceae). The chemical structure of isolated compounds 1-3 were elucidated on the basis of spectroscopic evidence (UV, IR, NMR) and comparison with those compound previouly reported.DOI: http://dx.doi.org/10.15408/jkv.v0i0.5037